Pengaruh Pengetahuan, Pengalaman, Skeptisme Profesional, Dan Intuisi APIP Dalam Mendeteksi Kecurangan Pada Inspektorat Provinsi NTB - Idham, Muhammad; Furkan, Lalu M.; Pituringsih, Endar (E-Jurnal Akuntansi; Vol 31 No 12 (2021), 2021)
This study aims to analyze the effect of knowledge, experience, professional skepticism, and intuition of government internal supervisors in detecting fraud at the NTB Provincial Inspectorate. Respondents from this study as many as 49 people who have functional positions. The technique of collecting data is by using a questionnaire and collecting data by using the census method. The data analysis technique used multiple regression analysis. The results showed that professional experience and skepticism had a significant positive effect on Fraud Detection. Meanwhile, knowledge and intuition have a negative effect on Fraud Detection. The theoretical implication of this research is to strengthen the results of previous studies that knowledge, experience, professional skepticism and intuition have an influence on fraud detection. The practical implications of this research are useful as a means to provide information or references for auditors, especially those who have an auditor's functional position. Meanwhile, the implications of research policies can be used as benchmarks and evaluations related to fraud detection in improving the quality and performance of auditors as government internal supervisors. Keywords : Knowledge; Experience; Profesionalisme Skepticism; Intuition; Fraud Detection.